BUILDING AN INCLUSIVE AND TOLERANT SOCIETY FOR MULTICULTURAL EDUCATION - Hendar; Rahman Tanjung (International Journal of Teaching and Learning, 2024)
This comprehensive literature review explores the multifaceted dimensions of optimizing building an inclusive and tolerant society towards multicultural education. The importance of building an inclusive society with multiculturalism education is the key to creating a society that is just, harmonious and ready to face the challenges of today. In an era of globalization and increasingly real diversity, multicultural education plays an important role in preparing the younger generation to interact in an increasingly connected world. The link between an inclusive society and multiculturalism educational policies lies in joint efforts to create an environment that accepts and promotes equality. Multiculturalism education policy is a tool used in education to achieve an inclusive society. The development of an inclusive society towards multicultural education involves a series of steps and principles designed to create an inclusive educational environment and promote equality. Multiculturalism education policies help remove barriers that hinder social and cultural inclusion. This creates better understanding between different cultural groups and reduces discrimination.